2020
DOI: 10.4081/or.2020.8658
|View full text |Cite
|
Sign up to set email alerts
|

Hand’s aneurysmal bone cyst: A rare localization. Case report and systematic literature review

Abstract: Aneurysmal bone cysts are benign, rare bony tumours frequently observed among children and young adults principally located in the long bones, pelvis, and spine and rarely in other anatomical district such as the hand. We report the case of a 12-year-old girl with an aneurysmal bone cyst, in active stage, involving the still-open epiphysis of the fourth metacarpal of the right hand, which was in a first time treated by curettage, and 3 months later, occurring a recurrence, by a radically excision of the bone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…1,3 A systematic review showed that more aggressive approaches with tumor resection and reconstruction with an autologous bone graft bring the best outcomes. 3 En bloc resection with reconstruction of the bone deficit is a more aggressive therapeutic option but has been shown to be associated with the lowest recurrence rate. 1,2 The morbidity associated with this more ambitious procedure raises concern, 2 and this procedure is usually reserved for patients with lesions that disrupt bone in periarticular regions 1,4 or with recurrent lesions resistant to other treatments.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,3 A systematic review showed that more aggressive approaches with tumor resection and reconstruction with an autologous bone graft bring the best outcomes. 3 En bloc resection with reconstruction of the bone deficit is a more aggressive therapeutic option but has been shown to be associated with the lowest recurrence rate. 1,2 The morbidity associated with this more ambitious procedure raises concern, 2 and this procedure is usually reserved for patients with lesions that disrupt bone in periarticular regions 1,4 or with recurrent lesions resistant to other treatments.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 There are several treatment modalities available to treat aneurysmal bone cysts, [1][2][3][4] but no generally accepted consensus on the best regimen. 1,3 A systematic review showed that more aggressive approaches with tumor resection and reconstruction with an autologous bone graft bring the best outcomes. 3 En bloc resection with reconstruction of the bone deficit is a more aggressive therapeutic option but has been shown to be associated with the lowest recurrence rate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations